Generalized practical stability results by perturbing Lyapunov functions. (1996) - Stutson, Donna; Vatsala, A. S.
Abstract : It is known that practical stability is neither stronger nor weaker than Lyapunov stability. In this paper we combine perturbing Lyapunov technique with stability in terms of two measures to obtain nonuniform practical stability results under weaker assumptions. We also use comparison methods to obtain these results.